Study on the structural characteristics of the Yangdachengzi oil layer in the Quantou Formation, ZY block, central depression, Songliao Basin - He, Chunyu; Lin, Yani; Zhang, Tianze; Ma, Jisheng; Li, Yunfei; Cheng, Jiaju; Zhang, Yinde (Frontiers in Earth Science, 2023)
Songliao Basin is a large Mesozoic-Cenozoic continental basin with multiple sedimentary cycles. It has experienced the influence of multidirectional and different structural stresses in the peripheral structural belt, resulting in the complex geological structure. The continental clastic deposits at the depression of Quantou Formation in the shallow part of the basin, including the Fuyu oil layer and the Yangdachengzi oil layer, are the primary exploration and development target. The structure and faults are the dominant factors controlling the hydrocarbon accumulation in the upper member of the Quantou Formation in the central Songliao Basin. In this study, we finely interpret the three-dimensional structure of the third member of Quantou Formation in the ZY block by the integration of well logging and seismic data, then analyze the stratigraphic distribution and fracture characteristic, and the tectonic development history of the Yangdachengzi oil layer. The results show that the Yangdachengzi oil layer is a monoclinic structure from southeast to northwest. It has four third-level structural units: the Mofantun nose structure, the Yumin nose structure, the Zhaoyuan nose structure, and the Zhaoyuan western nose structure, which form the structure-lithostratigraphic trap zones in the study area. In which, total of 80 traps for Yangdachengzi oil layer has been identified with the total area about 58.06 km2. Faults are highly developed in the central depression of the Songliao Basin. The ZY block is dominated by the extensional-strike-slip faults. The main fault direction is mostly north-northeast, and the secondary fault direction is mostly north-northwest. The complex tectonic activities determine the formation mechanism and the evolution of faults. The faults in this block can be classified as early-stage, middle-stage, late-stage, and long-term faults. The long-term fault is the major fault type of the five fault bundles, it acts as the main channel for oil and gas migration. And the reservoir is above-generation and below-storage model. This study provides evidence for the hydrocarbon accumulation model of the Quantou Formation.